Consumer Trends on Bulgarian Beer Market Driven by Covid-19 - Slavchev, Ivan (Research Papers, 2023)
The COVID-19 pandemic has changed the way of life of people in Bulgaria. Consumer expectations show a rapid metamorphosis, adapting to the new reality. The beer market, as part of the country’s economy, is a function of the ongoing macro and micro processes in Bulgaria. The worsening demographic crisis, the lack of foreign tourist’s flow and physical restrictions imposed by the government have significantly changed consumer behavior. COVID-19 clearly shows that the role and importance of market research is increasing exponentially. Only through market research the business can create sustainable strategies that lead to growth.